2020
DOI: 10.1039/d0fo00821d
|View full text |Cite
|
Sign up to set email alerts
|

Sauce it up: influence of condiment properties on oral processing behavior, bolus formation and sensory perception of solid foods

Abstract: Foods are rarely consumed on their own. Food oral processing behavior and sensory perception of composite foods varying in properties were investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
0
8
0
2
Order By: Relevance
“…For example, eating rate was 65% lower for bread alone than bread with mayonnaise (lubrication) and 45% lower for potato alone than potato with mayonnaise. 23 Similarly, the eating rate for crackers increased 61% when crackers were consumed with mayonnaise and for bread, eating rate increased 58% when consumed with mayonnaise. 24 Previous studies used a carrier/ mayonnaise weight ratio of 1 : 1 (g/g), whereas the current study had an 11 : 1 weight ratio.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, eating rate was 65% lower for bread alone than bread with mayonnaise (lubrication) and 45% lower for potato alone than potato with mayonnaise. 23 Similarly, the eating rate for crackers increased 61% when crackers were consumed with mayonnaise and for bread, eating rate increased 58% when consumed with mayonnaise. 24 Previous studies used a carrier/ mayonnaise weight ratio of 1 : 1 (g/g), whereas the current study had an 11 : 1 weight ratio.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has shown that modifying a food's texture properties offers an effective strategy to moderate eating rate and subsequent energy intake, as consumers adapt their oral processing behaviour and eating rate to the textures experienced during consumption. 14,15 Several studies to date have explored how food textural properties such as hardness, 7,16,17 chewiness, 18,19 viscosity, 9,20,21 lubrication [22][23][24] and the shape and size of food pieces [25][26][27][28][29][30][31] influence oral processing behaviour and eating rate. Findings indicate that not all texture manipulations have an equivalent impact on oral processing behaviour and eating rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, bread is usually consumed combined with other foods such as sauces (for example, gravy), or spreads (such as butter, cheese spread), which can also alter the breakdown pattern and thus, the oral behaviour, bolus properties, and sensory perception (van Eck, Fogliano, Galindo-Cuspinera, Scholten, & Stieger, 2019). Recent studies have shown how the addition of a sauce like mayonnaise facilitates the bolus formation (decreases the number of chewing cycles before swallowing), changing the perceived sensations, in special at the beginning of the oral processing (van Eck et al, 2020. This study's hypothesis was that the modification in the structure of gluten-free breads achieved by varying breadmaking conditions can affect the texture of the bread and its breakdown pattern in mouth, eliciting the dynamics of critical sensations during consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Já os temperos se referem aos produtos obtidos da mistura de especiaria s e de outros ingredientes, fermentados ou não, podendo ser designados por "condimento preparado" (B rasil, 2005). Essa definição está associada aos condimentos principalmente quanto a sua finalidade de modificação das características organolépticas, caracterizados pelos sentidos da visão, tato, paladar e olfato, que contribuem significativamente para a noss a ingestão diária de alimentos, uma vez que quando adicionados a algum tipo de alimento, os condimentos podem complementar ou aumentar a percepção dos seus sabores, além seu aspecto visual, aumentando assim o prazer sensorial (Van eck et al, 2020).…”
Section: Introductionunclassified